Physicochemical properties of Pinus massoniana wood subjected to silicone oil heat treatment - Edet OKON, Kufre; Ime UDOAKPAN, Ubong (Maderas. Ciencia y Tecnología, 2019)
In this Study, Pinus massoniana wood was heat treated with silicone oil to modify the chemical composition relative to the unmodified wood. Specifically, polysaccharide, lignin, extractives and ash contents were the properties investigated. The wood samples were first of all pre-heated in a micro-wave oven for 5 minutes to ease heat transfer within the wood. Silicone oil heat treatment was carried out at 150, 180 and 210oC for 2, 4, 8 h. The silicone oil heat treated wood was characterized by Fourier transformed infrared (FTIR), thermogravimetric analysis (TGA), X-ray diffraction (XRD) and contact angle. Results showed that silicone oil heat treatment caused significant decrease in the polysaccharide (P ˂ 0.0001) and ash contents (P ˂ 0.0001) and significant increase in the lignin (P ˂ 0.0001) and extractives contents (P ˂ 0.0001) as the treatment time increased. FTIR results showed that the chemical constituents of the wood were affected by the treatment, while TGA showed that the treated wood resulted in higher thermal stability with increase in the crystallinity index. Silicone oil heat treatment proved to be effective in increasing the contact angle of the wood.